Data Logger as Utility Meter Monitoring Device by Using Arduino: A Device to Improve the Utility Meter Monitoring Operation: A device to improve the utility meter monitoring operation. - NURUL IZZATI BINTI SULAIMAN; SULAIMAN, NURUL IZZATI; YAACOB, MEGAT SATRIA ZAINUDDIN (Progress in Engineering Application and Technology, 2021)
Generally, an energy meter, electrical meter, or utility meter is a device that is installed, at least, a unit in every building or premise for electrical usage monitoring and billing purposes. Unfortunately, as time moves forward, the need for innovation is necessary to cater to the circumstances, and having only those two abilities is no longer sufficient. For instance, in Malaysia, the current pandemic has interrupted the conventional method of collecting electricity usage data used by electricity generation companies, which have caused dissatisfaction and rage among end-users or the customers. Hence, this project is proposed to help overcome the complication faced by replacing the physical work of collecting data with a non-physical interface. The method used to conduct this project is through qualitative study whereby observations on customers' end were carried out, case studies on published researches, and a few others. This project's key findings are improving the utility meter monitoring efficiency and developing the Internet of Things (IoT) on it. It is strongly believed to be doable as there is also an initiative taken by an electrical generation company for a similar device, which simultaneously strengthens, even more, the belief in this project's success for the time being and the development of its future features.